Fe, Ru, and Os complexes with the same molecular framework: comparison of structures, properties and catalytic activities. (8th March 2017) - Yoshida, Masaki; Kondo, Mio; Okamura, Masaya; Kanaike, Mari; Haesuwannakij, Setsiri; Sakurai, Hidehiro; Masaoka, Shigeyuki
Abstract : A series of group 8 metal complexes with the same molecular framework, [M(PY5Me2 )L] n + (M = Fe, Ru, and Os; PY5Me2 = 2, 6-bis[1, 1-bis(2-pyridyl)ethyl]pyridine; L = monodentate ligand), were successfully synthesized and structurally characterized. The spectroscopic and electrochemical properties as well as the catalytic activity for water oxidation of these complexes were investigated.